2017
DOI: 10.1016/j.celrep.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

DOC1-Dependent Recruitment of NURD Reveals Antagonism with SWI/SNF during Epithelial-Mesenchymal Transition in Oral Cancer Cells

Abstract: The Nucleosome Remodeling and Deacetylase (NURD) complex is a key regulator of cell differentiation that has also been implicated in tumorigenesis. Loss of the NURD subunit Deleted in Oral Cancer 1 (DOC1) is associated with human oral squamous cell carcinomas (OSCCs). Here, we show that restoration of DOC1 expression in OSCC cells leads to a reversal of epithelial-mesenchymal transition (EMT). This is caused by the DOC1-dependent targeting of NURD to repress key transcriptional regulators of EMT. NURD recruitm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 45 publications
5
56
0
Order By: Relevance
“…SWI/SNF core subunits and RNA processing proteins were shared among the wild-type and SCCOHT SWI/SNF complexes (Figure 7). The wild-type SWI/SNF complex showed interactions with the NuRD chromatin remodeling and HDAC complex, consistent with previous reports that the NuRD complex interacts with SWI/SNF and shows functional antagonism in embryonic stem cells 55,56 and in oral squamous cell carcinoma cells 57 . The absence of SCCOHT SWI/SNF interactions with NuRD warrants future investigation of potential roles of NuRD in SCCOHT cells.…”
Section: Sccoht Residual Swi/snf Complex Shows Reduced Interactions Wsupporting
confidence: 91%
“…SWI/SNF core subunits and RNA processing proteins were shared among the wild-type and SCCOHT SWI/SNF complexes (Figure 7). The wild-type SWI/SNF complex showed interactions with the NuRD chromatin remodeling and HDAC complex, consistent with previous reports that the NuRD complex interacts with SWI/SNF and shows functional antagonism in embryonic stem cells 55,56 and in oral squamous cell carcinoma cells 57 . The absence of SCCOHT SWI/SNF interactions with NuRD warrants future investigation of potential roles of NuRD in SCCOHT cells.…”
Section: Sccoht Residual Swi/snf Complex Shows Reduced Interactions Wsupporting
confidence: 91%
“…Several studies, in both yeast and mammalian cells, point to cooperative or opposing activities of certain CRs (Gkikopoulos et al, 2011;Mohd-Sarip et al, 2017;Morris et al, 2014;Parnell et al, 2015;Rawal et al, 2018;Tomar et al, 2009;Yen et al, 2012).It is thus of interest to learn how the activities of the complete set of these enzymes are intertwined. Since RSC is the only yeast CR essential for cell viability, the activities of all other CRs in live cells have been studied predominantly by the use of deletion mutants.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently demonstrated that this is achieved in both ES cells and B‐cell progenitors by restricting access of transcription factors to regulatory sequences (Liang et al , ; Loughran et al , ; Bornelöv et al , ). Additionally, aberrations in expression levels of NuRD component proteins are increasingly being linked to cancer progression (Lai & Wade, ; Mohd‐Sarip et al , ).…”
Section: Introductionmentioning
confidence: 99%